Shocklets and short large amplitude magnetic structures (SLAMS) in the high mach foreshock of Venus - Collinson,GA; Hietala,H; Plaschke,F; Karlsson,T; Wilson,LB; Archer,M; Battarbee,M; BlancoCano,X; Bertucci,C; Long,D; Opher,M; Sergis,N; et al. (Geophysical Research Letters, 2023)
Shocklets and short large-amplitude magnetic structures (SLAMS) are steepened magnetic fluctuations commonly found in Earth's upstream foreshock. Here we present Venus Express observations from the 26th of February 2009 establishing their existence in the steady-state foreshock of Venus, building on a past study which found SLAMS during a substantial disturbance of the induced magnetosphere. The Venusian structures were comparable to those reported near Earth. The 2 Shocklets had magnetic compression ratios of 1.23 and 1.34 with linear polarization in the spacecraft frame. The 3 SLAMS had ratios between 3.22 and 4.03, two of which with elliptical polarization in the spacecraft frame. Statistical analysis suggests SLAMS coincide with unusually high solar wind Alfvén mach-number at Venus (12.5, this event). Thus, while we establish Shocklets and SLAMS can form in the stable Venusian foreshock, they may be rarer than at Earth. We estimate a lower limit of their occurrence rate of 14%.